Marketing communication management for micro, small and medium enterprises in increasing community economic empowerment - Amadeus, Prawira Amadeus Mayer Sutantio; Indra, Ricardo; Mani, La; Azhar, Karen Aulia; Ashari, Bunga Hurun (Enrichment : Journal of Management, 2023)
This literature review was conducted to explore the realm of marketing communications management in exploring its potential to increase the economic empowerment of communities in Indonesia. Using a qualitative descriptive approach, this research analyzes primary and secondary qualitative data obtained from trusted sources such as scientific journals, books and online or offline news. The results of research analysis reveal that empowerment of micro, small and medium enterprises (MSMEs) is a key factor in improving the welfare of society as a whole. This study also found that MSMEs play a major role in contributing to the country's gross domestic product (GDP) from year to year. Increasing gross domestic product (GDP) has an impact on Indonesia's economic progress. Indonesia's economic development is very dependent on MSMEs, so it is considered important to empower MSMEs with effective marketing communications management to increase productivity and reach a wider market. By utilizing various communication methods such as advertising, online marketing, direct marketing, personal selling, sales promotions, and public relations, MSMEs can improve their overall marketing strategy.